Answer
(3d² + 2g⁴)(9d⁴ - 6d²g⁴ + 4g⁸)
Explanation
We can factor out the following equation as follows:
27d⁶ + 8g¹² = 3³d⁶ + 2³g¹²
= (3d²)³ + (2g⁴)³
= (3d² + 2g⁴)((3d²)² - 3d²2g⁴ + (2g⁴)²)
= (3d² + 2g⁴)(9d⁴ - 6d²g⁴ + 4g⁸)
a. 64,672.318
b. 65,000
c. 64,672.32
d. 64,672.319
-2.2 x (-2) / (-1/4) x 5
Answer:
= 90 - 3n
Step-by-step explanation:
There is a common difference between consecutive terms, that is
84 - 87 = 81 - 84 = - 3
This indicates the sequence is arithmetic with nth term
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = 87 and d = - 3 , then
= 87 - 3(n - 1) = 87 - 3n + 3 = 90 - 3n
Answer: They will hike exactly 16 miles each day for 4 days.
Step-by-step explanation:
Given: Total distance to hike = 72 miles
They hike 16 miles per day.
Total days they will take to complete the distance =
It will take 4 complete days and a half day to complete the journey.
i.e. They will hike exactly 16 miles each day for 4 days.